Design and Simulation of Exoskeleton Robot - Guo, Zijian (International Journal of Mechanical and Electrical Engineering, 2024)
Based on the research of lower limb exoskeleton robots and extensive literature review, combined with human anatomy and kinematics, a four-degree-of-freedom lower limb exoskeleton robot was designed, and its three-dimensional model was established using UG software. In the design of the exoskeleton robot, it is required to have a simple structure, zero sensitivity in response speed, and be easy to realize automatic control. The exoskeleton robot designed in this paper uses electric push rods as the driving elements, and the dimensions of each part of the robot are obtained from the national standard human body size table; based on the analysis of the human gait cycle, and using cubic polynomial interpolation to plan the spatial posture of each joint; Adams was used to simulate the movement of the exoskeleton robot, and the motion curves of each joint were obtained.